2013
DOI: 10.3139/113.110296
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Chromium(III) Complex of Glycylphenylalanine with Ninhydrin in Aqueous and Cetyltrimethylammonium Bromide (CTAB) Micellar Media

Abstract: In this paper, we are reporting the influence of cationic CTAB surfactant on the interaction of chromium(III) complex of glycylphenylalanine [Cr(III)-Gly-Phe]2+ with ninhydrin under varying experimental conditions. The reaction follows irreversible first-order reaction kinetics with respect to [complex] and fractional-order with respect to [ninhydrin]. With progressive increase in [CTAB], the rate constant (k Ψ) for condensation of ninhydrin into [Cr(III)-Gly-Phe]2+ complex increased, reached… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Surfactants are broadly employed in a range of industrial, commercial, everyday life applications; as a result, their properties in aqueous solutions have received considerable attention . Sodium dodecylbenzenesulfonate (SDBS) is one of the anionic surfactant (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Surfactants are broadly employed in a range of industrial, commercial, everyday life applications; as a result, their properties in aqueous solutions have received considerable attention . Sodium dodecylbenzenesulfonate (SDBS) is one of the anionic surfactant (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the scheme, nucleophilic attack is not possible because the lone pair of electrons is not available in the zinc‐glycylglycine complex. Therefore, reaction starts through condensation of coordinated ninhydrin within the coordination sphere of metal ions (Kabir‐ud‐Din et al, ; Kumar et al, ; Kumar and Rub, ; Rafiquee et al, ). Therefore, the reaction occurs through inner sphere complexation on [Zn(II)‐Gly‐Gly] + with ninhydrin.…”
Section: Resultsmentioning
confidence: 99%
“…In the present case, this lone pair is not free. Therefore, condensation of the coordinated amino group of Gly-Tyr to the coordinated carbonyl group of ninhydrin occurs within the coordination sphere of copper(II) as shown in Scheme 1, which is an example of a template mechanism [19][20][21].…”
Section: Effect Of Temperature On the Reaction Ratementioning
confidence: 99%
“…Kabir-ud-Din et al has studied ninhydrin-amino acid reactions and found that the effect of surfactants, solvents and coordination to metal salts increases the rate of color formation [15][16][17]. However, studies on the reaction rate of ninhydrin-peptide have not attracted much attention [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%